Habilitation of Child with Spinal Muscular Atrophy Type 2: A Case Report - Marietta Shanti Prananta; Mirna Minarti Rahmawati; Rachmat Zulkarnain Goesasi (Faculty of Medicine, Universitas Airlangga, 2022)
Spinal Muscular atrophy (SMA) is a severe neuromuscular disorder which is a hereditary genetic disease. It is an incurable disease due to a defect in the survival motor neuron 1 (SMN1) gene. This report shows the benefit of rehabilitation intervention for the habilitation of a child with SMA Type 2. A 5-year-8-month-old female diagnosed with SMA by genetic testing complained of an inability to stand independently. Her rehabilitation problems were muscle power function, mobility of joint function, respiration function, exercise tolerance function, mobility, self-care, school education, and economic life. We provided rehabilitation programs with a regular follow-up for six months, including flexibility exercises, breathing exercises, cardiopulmonary endurance exercises, standing support exercises, wheeling exercises, and activities of daily living (ADL) exercise. We coordinated with a psychologist and social workers to assess the psychology and socioeconomic condition of the patient and caregiver. The muscle power function, which was evaluated by functional motor ability assessment using the Revised Hammersmith Scale for SMA (RHS), didn't show any deterioration, and she had improvement in the ADL capability. We resolved the mobility of joint function problem in this patient for the joint stiffness in both knees, and Cobb's angle of scoliosis was decreased. Respiration function assessed by peak cough flow and chest expansion showed an increase, and exercise tolerance function was also increased. The patient received some donations from donators to overcome economic issues assisted by a social worker for the activity chair, standing frame, and modified wheelchair. She could mobilize well using her own modified wheelchair, played with friends, and attended school. A follow-up by the psychologist showed good psychological conditions of the patient and family. The quality of life assessment of patients by PedsQL Neuromuscular Modul showed improved results, and the caregiver burden assessment by The Zarit Burden Interview had decreased. Rehabilitation intervention for the habilitation of a child with SMA Type 2 can maintain, restore, and promote the patient's functional ability to provide a better quality of life and control the caregiver burden.